2017
DOI: 10.1016/j.bbi.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Pinocembrin protects hemorrhagic brain primarily by inhibiting toll-like receptor 4 and reducing M1 phenotype microglia

Abstract: Neuroinflammation is a major contributor to intracerebral hemorrhage (ICH) progression, but no drug is currently available to reduce this response and protect against ICH-induced injury. Recently, the natural product pinocembrin has been shown to ameliorate neuroinflammation and is undergoing a phase II clinical trial for ischemic stroke treatment. In this study, we examined the efficacy of pinocembrin in an ICH model, and further examined its effect on microglial activation and polarization. In vivo, pinocemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
156
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 181 publications
(160 citation statements)
references
References 57 publications
4
156
0
Order By: Relevance
“…These results suggest that the ratio of IFNγ to M2-like cytokine levels might be a more reliable marker than IFNγ levels alone for the assessment of inflammatory status in the chronic phase after ICH. Our group has shown that M1 markers such as CD16, CD32 and iNOS are highly expressed on microglia on days 1 and 3 after ICH 62 , suggesting that M1-like microglial polarization occurs early in the acute phase.…”
Section: Microgliamentioning
confidence: 86%
“…These results suggest that the ratio of IFNγ to M2-like cytokine levels might be a more reliable marker than IFNγ levels alone for the assessment of inflammatory status in the chronic phase after ICH. Our group has shown that M1 markers such as CD16, CD32 and iNOS are highly expressed on microglia on days 1 and 3 after ICH 62 , suggesting that M1-like microglial polarization occurs early in the acute phase.…”
Section: Microgliamentioning
confidence: 86%
“…In addition, we employed Nrf2 KO mice to investigate whether the neuroprotective effects of SalB occur via Nrf2 signaling. Mice were anesthetized with isoflurane (4.0% for induction, 2.0% for maintenance) and ventilated with oxygen-enriched air (20%:80%) via a nose cone, as in our previous studies [38,39]. After anesthetization, a burr hole was drilled into the skull 4.5 mm anterior to the bregma.…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral edema was reflected by the brain water content, which was calculated as described previously [47, 48]. We sacrificed six mice per group to assess brain water content at day 7.…”
Section: Methodsmentioning
confidence: 99%